2016
DOI: 10.1007/s12663-016-0953-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of C-Reactive Protein and WBC Count in Fascial Space Infections of Odontogenic Origin

Abstract: The findings of this prospective analysis indicate that White blood cells and C-reactive protein are effective markers for determining severity of infection, efficacy of treatment regime for patients with fascial space infections of odontogenic origin. Thus the markers also help in making treatment of patients with fascial space infections of odontogenic origin more cost effective and they also help protecting patients from side effects of excess drugs usage. Thus we conclude that CRP should be incorporated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
1
19
1
2
Order By: Relevance
“…CRP, WBC count and body temperature correlated with the clinical improvement, and their decrease toward the reference range signifies the resolution of infection. The results of the present study are further supported by Bali et al [19] and Bagul et al [20] who in their respective studies concluded that CRP and WBC count acted as good guide for determining the severity of infection in patients with fascial space infections of odontogenic origin.…”
Section: Discussionsupporting
confidence: 86%
“…CRP, WBC count and body temperature correlated with the clinical improvement, and their decrease toward the reference range signifies the resolution of infection. The results of the present study are further supported by Bali et al [19] and Bagul et al [20] who in their respective studies concluded that CRP and WBC count acted as good guide for determining the severity of infection in patients with fascial space infections of odontogenic origin.…”
Section: Discussionsupporting
confidence: 86%
“…9,11,28 In this study, 66.67% of patients did not have comorbid or signs of dehydration. This is not in accordance with the research conducted by Bagul et al 26 in 2016 which stated that odontogenic infections generally have comorbid predisposing factors, for example: diabetes mellitus, obesity, immunosuppression or arterial hypertension which have systemic consequences. 25 In addition to comorbid factors, Bagul et al 26 also explained that the severity of odontogenic infections could be due to other factors such as advanced adulthood, tobacco smoking habits, drug abuse, poverty and patients with poor social conditions which can also cause a decline in the immune system.…”
Section: Discussioncontrasting
confidence: 86%
“…The condition of trismus and dysphagia is a clinical parameter that can detect signs of respiratory tract obstruction. 26,27 From the results of clinical examination to see involvement of facial space, it was found 63.33% of patients who had involvement of more than one facial space, and 80% of them suffered infections in the submandibular space, which consistent with research conducted by Opitz et al 25 and Heim et al 20 explaining that mandibular molar teeth are the most common focus of infection in odontogenic infections because their root tips reach the mylohyoid muscle so that without proper management of the periapical infections can spread to the submandibular space or parapharyngeal space. 28,29 The involvement of more than one space can occur due to the delay of the patient in seeking appropriate treatment for odontogenic infections.…”
Section: Discussionmentioning
confidence: 99%
“…The high WBC counts in the SCD population could be as a result from infections or reactions to medications. 22 , 23 Evaluation of WBCs should be performed periodically in primary health care clinics to identify patients with lower or higher values than the normal WBC range. This may enable hematologists to assess the current medications, underlying etiology, or impending SCD crisis and initiate treatment to mitigate symptoms and modifiable factors that are associated with high WBCs.…”
Section: Discussionmentioning
confidence: 99%